Mung bean sprout (Phaseolus aureus) nuclease and its biological and antitumor effects - Soucek, J; Skvor, J; Poucková, P; Matousek, J; Slavík, T; Matousek, J (Neoplasma, 2006)
Bovine seminal ribonuclease (BS RNase), a dimeric homolog of bovine pancreatic ribonuclease (RNase A), is known to display special biological activities namely cytotoxicity for human tumor cells. Because some plant ribonucleases have a similar mass weight and structure as the animal ribonuclease, effects of a commercial product of Mung bean (Phaseolus aureus) nuclease (PhA) were studied on proliferation of ML-2 human tumor cells, as well as it's aspermatogenic, embryotoxic, immunogenic, and immunosuppressive activity, and therapeutic efficiency in athymic mice bearing human melanoma tumor. Concerning the antiproliferative activity, PhA nuclease was almost non-effective in vitro on ML-2 cells and also immunosuppressive activity on human lymphocyte in mixed culture was very low compared to that of BS RNase. However, significant antitumor activity was detected on human melanoma tumor after intratumoral or intraperitoneal administration into the mice. Furthermore conjugate of PhA nuclease with polyethylene glycol (PEG) injected seven times at the dose of 10 microg intraperitoneally showed identical antitumor activity as that of bovine seminal ribonuclease (BS RNase) injected by the same way at ten times higher dose. Both PhA and BS RNases exerted strong aspermatogenic effect on the width of spermatogenic layers while RNase A administration at ten times higher concentration was ineffective. PhA nuclease when compared by means of antibody cross reaction with RNase A, BS RNase and wheat leaf neutral RNase (WLN-RNase) was found to be immunologically similar to RNase A and WLN-RNase, meanwhile BS RNase showed much higher antigenicity in comparison with them.
Keywords: nádorové buněčné linie; Phaseolus; teratogeny; Single-Strand Specific DNA and RNA Endonucleases; lidé; experimentální nádory; Ribonuclease, Pancreatic; mužské pohlaví; Mice; Cell Proliferation; Cell Line, Tumor; Antineoplastic Agents; fazol; Mice, Nude; Antispermatogenic Agents; protinádorové látky; antispermatogenní látky; zvířata; Humans; Spermatogenesis; endonukleasy specifické pro jednořetězcové nukleové kyseliny; myši nahé; Neoplasms, Experimental; Embryo, Mammalian; pankreatická ribonukleasa; myši; embryo savčí; proliferace buněk; Spermatozoa; spermatogeneze; Teratogens; spermie; Male; Animals